The Conserved ESCRT-III Machinery Participates in the Phagocytosis of Entamoeba histolytica - Avalos-Padilla, Yunuen; Knorr, Roland L.; Javier-Reyna, Rosario; García-Rivera, Guillermina; Lipowsky, Reinhard; Dimova, Rumiana; Orozco, Esther (Frontiers in Cellular and Infection Microbiology, 2018)
The endosomal sorting complex required for transport (ESCRT) orchestrates cell membrane-remodeling mechanisms in eukaryotes, including endocytosis. However, ESCRT functions in phagocytosis(ingestion of ≥ 250 nm particles), has been poorly studied. In macrophages and amoebae, phagocytosis is required for cell nutrition and attack to other microorganisms and cells.In Entamoeba histolytica, the voracious protozoan responsible for human amoebiasis, phagocytosisis a land mark of virulence. Here, we have investigated the role of ESCRT-III in the phagocytosis of E. histolytica, using mutant trophozoites, recombinant proteins (rEhVps20, rEhVps32, rEhVps24 and rEhVps2) and giant unilamellar vesicles (GUVs). Confocal images displayed the four proteins located around the ingested erythrocytes,in erythrocytes-containing phagosomes and in multivesicular bodies. EhVps32 and EhVps2 proteins co-localized at the phagocytic cups.Protein association increased during phagocytosis. Immunoprecipitation and flow cytometry assays substantiated these associations. GUVs revealed that the protein assembly sequence is essential to form intraluminal vesicles (ILVs). First, the active rEhVps20 bound to membranes and recruited rEhVps32, promoting membrane invaginations. rEhVps24 allowed the detachment of nascent vesicles, forming ILVs; and rEhVps2 modulated their size. The knock down of Ehvps20 and Ehvps24genes diminished the rate of erythrophagocytosis demonstrating the importance of ESCRT-III in this event. In conclusion, we present here evidence of the ESCRT-III participation in phagocytosis and delimitate the putative function of proteins, according to thein vitro reconstruction of their assembling.